2022
DOI: 10.51731/cjht.2022.419
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Continuous Glucose Monitoring for People Living With Type 1 Diabetes

Abstract: Continuous glucose monitoring (CGM) is a method of glucose testing in which a sensor is inserted into the skin and continuously monitors interstitial glucose concentrations. Real-time continuous glucose monitoring (rtCGM) systems automatically measure glucose and display a recent glucose value. Evidence suggests that rtCGM may improve hemoglobin A1C and time in range in adults and pediatric patients with type 1 diabetes, but this is uncertain. Limited evidence suggests that in people with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Evidence from a cost-effective analysis conducted in Spain suggested that glycemic monitoring with rtCGM was not cost-effective compared to SMBG alone in individuals living with T2D. 18 A recent CADTH report 23 on the clinical effectiveness and cost-effectiveness of rtCGM compared to SMBG in T1D found that rtCGM is favoured over SMBG for glycemic monitoring in adults and pediatric patients. rtCGM was also found to be cost-effective compared to SMBG at a WTP threshold of $50,000 per QALY.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%
“…Evidence from a cost-effective analysis conducted in Spain suggested that glycemic monitoring with rtCGM was not cost-effective compared to SMBG alone in individuals living with T2D. 18 A recent CADTH report 23 on the clinical effectiveness and cost-effectiveness of rtCGM compared to SMBG in T1D found that rtCGM is favoured over SMBG for glycemic monitoring in adults and pediatric patients. rtCGM was also found to be cost-effective compared to SMBG at a WTP threshold of $50,000 per QALY.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%